A Pilot Study of Application of the Stroke Riskometer Mobile App for Assessment of the Course and Clinical Outcomes of Covid-19 Among Hospitalised Patients - Merkin, Alexander; Akinfieva, Sofya; Medvedev, Oleg N; Krishnamurthi, Rita V; Gutsaluk, Alexey; Reips, Ulf-Dietrich; Kuliev, Rufat; Dinov, Evgeny; Nikiforov, Igor; Shamalov, Nikolay; Shafran, Polina; Popova, Lyudmila; et al. (Karger Publishers, 2023)
BACKGROUND: Early determination of COVID-19 severity and health outcomes could facilitate better treatment of patients. Different methods and tools have been developed for predicting outcomes of COVID-19, but they are difficult to use in routine clinical practice. METHODS: We conducted a prospective cohort study of inpatients aged 20-92 years, diagnosed with COVID-19 to determine whether their individual 5-year absolute risk of stroke at the time of hospital admission predicts the course of COVID-19 severity and mortality. The risk of stroke was determined by the Stroke Riskometer mobile application. RESULTS: We examined 385 patients hospitalised with COVID-19 (median age 61 years). The participants were categorised based on COVID-19 severity: 271 (70.4%) to the "Not severe" and 114 (29.6%) to the "Severe" groups. The median risk of stroke the next day after hospitalisation was significantly higher among patients in the Severe group (2.83 [95% CI 2.35-4.68]) vs the Not severe group (1.11 [95% CI 1.00-1.29]). The median risk of stroke and median systolic blood pressure (SBP) were significantly higher among non-survivors (12.04 [95% CI 2.73-21.19]) and (150 [95% CI 140-170]) vs survivors (1.31 [95% CI 1.14-1.52]), 134 [95% CI 130-135]), respectively. Those who spent more than 2.5 hours a week on physical activity were 3.1 times more likely to survive from COVID-19. Those who consumed more than one standard alcohol drink a day, or suffered with atrial fibrillation, or had poor memory were 2.5, 2.3, and 2.6 times more likely not to survive from COVID-19, respectively. CONCLUSIONS: High risk of stroke, physical inactivity, alcohol intake, high SBP, and atrial fibrillation are associated with severity and mortality of COVID-19. Our findings suggest that the Stroke Riskometer app could be used as a simple predictive tool of COVID-19 severity and mortality.
Keywords: Prevention; Clinical Research; Cardiovascular; Stroke; Brain Disorders; Neurosciences; Rehabilitation; 4 Detection, screening and diagnosis; 4.2 Evaluation of markers and technologies; Stroke; Cardiovascular; 3 Good Health and Well Being